Assessment of Growth and Yield of Maize through Integrated Nutrient Management Practices - Aman Yadav; V. V. Panchal; A. A. Kawade (Archives of Current Research International, 2024)
A field trial was conducted at experimental cum demonstration field, Shri Vaishnav Institute of Agriculture, Shri Vaishnav Vidyapeeth Vishwavidyalaya, Indore, Madhya Pradesh during the year 2023-24 to study the effect of integrated nutrient management on growth and yield of maize. The treatment consisted of integrated nutrient management viz., T1: Absolute control, T2: 100 % RDF (100:60:40 kg N, P2O5, K2O ha-1), T3: 50 % RDF + 50 % RDN through FYM, T4: 50 % RDF + 50 % RDN through Vermicompost, T5: 75 % RDF + 25 % RDN through FYM, T6: 75 % RDF + 25 % RDN through Vermicompost, T7: 100 % RDN through FYM and T8: 100 % RDN through Vermicompost. The experiment was laid out in a randomized block design (RBD) with eight treatment combinations and replicated three times. The various growth and yield characters were studies during the results and found that, application of 75 % RDF + 25 % RDN through vermicompost recorded significantly maximum growth characters viz., plant height plant-1 (294.33 cm), number of functional leaves plant-1 (7.90) and leaf area plant-1 (34.73 dm2) and yield attributes viz. length of cob with husk and without husk, diameter of cob with and without husk, weight of cob with (20.50 cm) and without husk (16.83), number of cobs plant-1 (1.40) and weight of grain cob-1 with (213.33 g) and without husk (205.33 g) and yield viz., grain yield (61.55 q ha-1) and dry fodder yield (69.76 q ha-1) as compared to rest of the treatments. However, absolute control treatment recorded maximum number of days for 50 % tasseling (69.33) and 50 % silking (73.33).